Analisis Eksplorasi Tambang Ilegal di Kampung Kalian Luar, Kabupaten Kutai Barat: Analysis of Illegal Mining Exploration in Kalian Luar Village, West Kutai District - Muhammad Jamal Amin; Adam Idris; Badruddin Nasir; Novianus Lasah (Program Studi Ilmu Pemerintahan Fisip Universitas Mulawarman, 2021)
This research examines “illegal” mining in Kalian Luar village, West Kutai District. This research employed descriptive qualitative method with data collection carried out through interviews, observation, and documentary study. Research findings show that “illegal” mining occurs due to the existence of a village government rule legalizing community mining, despite District Regulations prohibiting such mining. This reflects the absence of coordination between District and Village governments, impeding the proper implementation of mining regulations. Community members being uninformed or misinformed about local mining regulations, combined with the absence of sanctions, allow continuation of such mining activities.